Sophisticated Glass Tapes for Fabrication of Composites (Journal of Fiber Bioengineering and Informatics, 2019)
The mechanical properties of fabrics derived from glass tows are excellent. They can be used forreinforcement of composites. In this work, glass fiber based stabilized hybrid composite tapes (SHCT)containing special types of resins which could be used for preparation of composites using precise windingtechnique was prepared. The resins were loaded by suitable types of nanoparticles that would enhancemechanical properties. Detailed investigation of tensile forces like breaking force, deformation at breakand initial modulus was conducted. The results showed a significant difference between the samples.This research achieved loading of resins without its penetration into the winded structure through tightand complicated arrangement of fibrous phase. The tapes were found to be durable that enables theirlong-term storage and their sustained fit-to-use after extended storage times.
Keywords: Hybrid Tapes; Tensile Properties; Precise Winding; Composites; Epoxy Resin